PENGARUH SUPLEMENTASI MADU KLANCENG DAN TEPUNG MAGGOT TERHADAP PRODUKTIVITAS PUYUH: THE EFFECT OF SUPPLEMENTATION OF STONE HONEY AND MAGGOT FLOUR ON QUAIL PRODUCTIVITY - Faizin, Wahid Nur; Wulandari, Eudia Christina; Purwadi, Purwadi (Tropical Animal Science, 2025)
The use of natural feed such as immunostimulants and alternative protein sources has been proven to efficiently improve poultry performance. This study examined the effect of Klanceng honey in the starter phase and Black Soldier Fly (BSF) maggot meal in feed on the productivity of local quail (Coturnix coturnix japonica). The study was conducted in Boyolali on December 24, 2024–February 9, 2025, using a Completely Randomized Design (CRD) with 4 treatments and 5 replications, involving 100 female quail. The treatments consisted of control (T0) and the addition of 5% (T1), 10% (T2), and 15% (T3) maggot meal, as well as 1% klanceng honey through drinking water in the starter phase. Maintenance was carried out from 1 day to 48 days of age. The parameters observed included feed consumption, PBB, FCR, SGR, egg-laying age, and mortality. Data were analyzed using ANOVA and Duncan's test (? = 5%). The results showed that the treatments significantly affected almost all parameters, except mortality. Treatment T3 gave the best results. It was concluded that klanceng honey and maggot meal were effective as functional feed to increase quail productivity. The results showed that administration in the P2 treatment significantly impacted quail productivity. The combination of klanceng honey and maggot meal was effective as a functional feed to improve the performance and efficiency of quail farming sustainably.